(untitled) - Ricvhard N McDonald (Winnipeg, Canada, 1993)
This book attempts to develop the adeas of structure and reactivity of organic compounds via a gradual extension of thge adeas the student is already familiar with. It of 15 chapters. The first five chapters present the underlying principles and the broad outlines of the reasoning involved in deducting the behavior of organic molecules. Althrough there is a certain amount of detail involved in the ideas of bonding, isomerism, and the drawing of resoncance forms, the principal emphasis is on the broad aspects of the theory. Chapters 7 through 13 extend and particularize the deductive process to encompass those particular facts. The last two chapters deal with material which important because of the role it plays in biochemistry and industrial technology
Keywords: chemistry, organic